If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = 18 + -3x Solving 42 = 18 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 42 + 3x = 18 + -3x + 3x Combine like terms: -3x + 3x = 0 42 + 3x = 18 + 0 42 + 3x = 18 Add '-42' to each side of the equation. 42 + -42 + 3x = 18 + -42 Combine like terms: 42 + -42 = 0 0 + 3x = 18 + -42 3x = 18 + -42 Combine like terms: 18 + -42 = -24 3x = -24 Divide each side by '3'. x = -8 Simplifying x = -8
| -2/3(3/2a-1)+5/6 | | 6x^2-11x=5 | | 9p+6=14+8p | | -3/4a=-5/8 | | 6(5/7+4/63) | | X(6x-11)=5 | | 4(x+2)+2(x-7)-3(x+1)= | | p=6-2q | | 1=-5(4x+2)+21x | | -1/3q=2/3 | | 8x-10=8x+11 | | -24=11v | | 5a+3-b+1= | | 2/3-1/8 | | 4=18+7x | | 1=(4x+2)+21x | | 2(a+b)+3(2b-4a)= | | 3x-12/6=-5 | | 133x+32=87 | | 2x+3+6-5x-7-x+12+10-7x+4x= | | -sin^2=2cosx-2 | | 2(5+3+9)= | | 13x+5-3x=5x-45 | | 133x+31=87 | | 7lbs=2.96 | | 6-4(x-3)=2x-24 | | 133x+30=87 | | 7p=2.96 | | 22*2.5= | | 6x-5=8-9x | | 133x+y=87 | | -2x+4+8x=14 |